2017
DOI: 10.1038/s41598-017-09350-7
|View full text |Cite
|
Sign up to set email alerts
|

An oxytocin-dependent social interaction between larvae and adult C. elegans

Abstract: Oxytocin has a conserved role in regulating animal social behaviour including parental-offspring interactions. Recently an oxytocin-like neuropeptide, nematocin, and its cognate receptors have been identified in the nematode Caenorhabditis elegans. We provide evidence for a pheromone signal produced by C. elegans larvae that modifies the behaviour of adult animals in an oxytocin-dependent manner increasing their probability of leaving a food patch which the larvae are populating. This increase is positively co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 53 publications
(93 reference statements)
4
59
0
Order By: Relevance
“…B) Ants were collected from foraging area (foragers) and brood chamber (nurses) from the same nest (n = 20, Student's t test). C ) Relative expression ratio of a precursor before (d 0), during (d 2), and after (d 3 and 9) the starvation period of 48 h (n = [17][18][19][20]. See detailed statistical analyses in Supplemental Table 5.…”
Section: Analysis Of Behavioral Changes In Ip-kd Ants Of L Neglectusmentioning
confidence: 99%
See 1 more Smart Citation
“…B) Ants were collected from foraging area (foragers) and brood chamber (nurses) from the same nest (n = 20, Student's t test). C ) Relative expression ratio of a precursor before (d 0), during (d 2), and after (d 3 and 9) the starvation period of 48 h (n = [17][18][19][20]. See detailed statistical analyses in Supplemental Table 5.…”
Section: Analysis Of Behavioral Changes In Ip-kd Ants Of L Neglectusmentioning
confidence: 99%
“…In these worms, OT/VP-like (nematocin) signaling controls mate searching and mating behaviors in males as well as gustatory learning processes that regulate food preference (15, 16). In addition, nematocin appears to regulate parental–offspring social behavior (17). …”
mentioning
confidence: 99%
“…On the one hand, if the signal is completely abolished then measurement is impossible. On the other hand, knowing that a given treatment affects bacterial physiology may be useful information in interpreting any observed feeding differences, since drug effects on bacteria are known to also affect host physiology (Cabreiro et al 2013; Scott et al 2017; García-González et al 2017). Another limitation of our method is its sensitivity: we were unable to detect single worm feeding, although this is likely to be possible using a higher magnification imaging system.…”
Section: Discussionmentioning
confidence: 99%
“…Feeding behaviour plays an important role in fields ranging from ecology and evolution (Larsen 2003; MacArthur and Pianka 1966) to ageing and metabolism (Balasubramanian, Howell, and Anderson 2017; Trepanowski et al 2011) and health and disease (Djalalinia et al 2015; Mattson et al 2014). The roundworm C. elegans has emerged as a useful model organism to study all aspects of feeding, including worms’ immediate response to finding food (Sawin, Ranganathan, and Horvitz 2000), foraging and patch leaving (Shtonda 2006; Harvey 2009; Bendesky et al 2011; Milward et al 2011; E. Scott et al 2017), as well as the details of food intake (L. Avery 1993; Leon Avery and Shtonda 2003; Fang-Yen, Avery, and Samuel 2009) and even spitting (Bhatla et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have shown that L1 arrest density can alter various phenotypes in C. elegans. For example, L1 density plays a role in parent-offspring signaling, as the presence of L1 larvae on plates was recently shown to alter food-related behaviors in adults (SCOTT et al 2017). In this case, the relevant signal is lost in daf-22 mutant, indicating that ascarosides are likely responsible for L1 density signaling.…”
Section: L1 Density Signaling In C Elegansmentioning
confidence: 99%